PENGEMBANGAN E-BOOK INTERAKTIF PADA MATERI KOMPUTER GRAFIS MATA PELAJARAN DASAR DESAIN KOMUNIKASI VISUAL KELAS DI SMKN-1 SIJUNJUNG - Wilda Turahma; Heri Mulyono; Bernediv Nurdin (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
The problem in this study is that teachers still use a lot of printed learning media, printed books make the learning process less interesting. Visual communication design learning so far tends to use static presentation methods, as well as video tutorials that are less interactive so that student learning motivation tends to vary and low student understanding of the material. The purpose of this study was to produce an interactive E-book in the Computer Graphics material at SMKN 1 Sijunjung in the Basic Visual Communication Design subject. This study uses the Research and development method. The development model used in this study is the ADDIE model. The research subjects involved in the Basic Visual Communication Design subject in the 2025/2026 academic year totaling 23 people and 2 teacher responses. The research instrument is a validity instrument using a validity questionnaire with 5 validators. The validity assessment contains 3 people for media validators and 2 people for material validators. The practicality instrument uses a student response questionnaire of 23 people and 2 teachers. The product produced in this study is an interactive E-book. Based on the media validity results, the validation score was 92.64%, categorized as "Very Valid." The material validity score was 88.47%, categorized as "Very Valid." Therefore, it can be concluded that the interactive e-book is "Very Valid" in terms of validity. Based on the teacher's practicality score, the score was 88.88%, categorized as "Very Practical." The student's practicality score was 84.25%, categorized as "Very Practical."